Iranian pre‐hospital emergency care nurses' strategies to manage workplace violence: A descriptive qualitative study. (6th June 2019) - Dadashzadeh, Abbas; Rahmani, Azad; Hassankhani, Hadi; Boyle, Malcolm; Mohammadi, Eisa; Campbell, Suzanne
Abstract: Aim: To explore the experiences of Iranian nurses working in pre‐hospital emergency care services and the strategies used to manage of workplace violence. Background: Pre‐hospital emergency nurses are subject to workplace violence; however, little research addresses their experiences, particularly related to their strategies in dealing with workplace violence. Methods: A descriptive qualitative study that involved nineteen male nurses who were working in pre‐hospital services collected data using semi‐structured interviews and analysed it using qualitative content analysis. Results: Data analysis yielded four descriptive categories including no reaction to violence (tolerance and acceptance as common workplace conflicts), situational management (patient and scene management), confrontation (direct and indirect) and escaping the scene. Patient management was the dominant strategy used and had the best outcomes related to both patient and personnel safety. Conclusion: This study showed that pre‐hospital nurses use different strategies to manage violence and patient management was a common and useful strategy for managing workplace violence. However, the pre‐hospital nurses have little training, insufficient support and are poorly prepared to manage workplace violence. Implications for Nursing Management: The development of context‐based guidelines, continuing education, better‐equipped ambulances that include medical and defence equipment, as well as better coordination of the police force in ambulance operations, can help to reduce workplace violence.